REFLECTIONS ABOUT THE RELATIONSHIPS BETWEEN ART AND TECHNOLOGY (Fiep Bulletin - online, 2015)
The present work intended to investigate the relationships among art, science and technology, taking the hybrid dance as a possibility of developing this analysis. For so much a descriptive-exploratory research, of bibliographical nature , was built using a case study developed starting from the proposal of the company of dance "Cena 11", as an exemplary field for this analysis. In this article we emphasized two axes for the analysis of this content: The dance of the techniques: physical perception and classic in the art of the "Cena 11", being constituted the analysis of the physical preparation of the group; The function of the technology attached to the body in the shows of the group, that characterized the analysis in the way as the art of the group comes to the audience.
Keywords: Art; hybrid dance and technology